Right para duodenal hernia presenting as small bowel obstruction: a rare case report - Kakkar, Dipanshu; Kochar, Shubra; Prasad, Sanjeev (International Surgery Journal, 2020)
Internal hernias are rare congenital anomalies. The most common internal hernias are para duodenal hernias (53%) followed by pericaecal hernias 13%. Para duodenal hernia, a rare congenital anomaly that arises from an error of rotation of the midgut, is the most common type of intra-abdominal hernia. There are two types, right and left para duodenal hernia, the right being less common. Here we present a case of a 21 years old male presented in surgical emergency department non-passage of flatus and stools since, 5 days with associated nausea, vomiting and abdominal pain. Abdominal CT demonstrated signs of small bowel obstruction. A midline laparotomy was performed. Intra operative findings suggestive of right sided para duodenal hernia. Careful reduction of hernia and plication of sacs done with new D-J flexure formation. Para duodenal hernias are rare congenital entities. Left para duodenal hernia is more common than right. The right para duodenal hernia occurs when the pre arterial limb of the mid gut loop fails to rotate around the superior mesenteric artery. Symptoms may vary according to degree of obstruction or gut ischemia. Reduction of contents of the sac and plication of the sac to prevent further hernia formation and resection of small bowel in cases of gut gangrene remains the mainstay of the treatment.